Komparasi Performansi Antara Proportional Integral Derivative Controller (PID) Dan Fuzzy Logic Controller (FLC) Pada Penjejak Cahaya Dengan Tiga Sensor - Gunawan, Doni; Away, Yuwaldi; Sara, Ira Devi; Novandri, Andri (P3M Politeknik Negeri Banjarmasin, 2022)
The technology of light tracking monitors the solar panels to track the sun with full efficiency, and the solar panels can be upright to the sunlight in order to maximize the absorption of solar energy, so this system has a higher efficiency than non-tracking systems. This study aimed to obtain a controller that works accurately between the Proportional, Integral, and Derivative Controller (PID) and the Fuzzy Logic Controller (FLC) Algorithm by comparing the performance of the two algorithms in regulating the direction of the light tracker to detect the presence of sunlight. This solar prototype uses nine lamps as a simulation to determine the accuracy and precision of the angles of the two light trackers. The parameters compared in this test were the aspects of angular velocity and angle accuracy. The mean value of angular velocity obtained from the PID light tracking test results was 0.16 rad/s and the average linear velocity was 0.092 m/s whereas in the FLC light tracker, the average angular velocity value was 0.207 rad/s. Tests using a PID light tracker resulted in an X-axis accuracy of 45% and a Y-axis accuracy of 30%. The FLC light tracker, on the other hand, had an X-axis accuracy of 80% and a Y-axis accuracy of 30%.The precision value obtained by the PID light tracker on the X axis was 45% and the Y axis was 38%, while the precision value obtained by the FLC light tracker on the X axis was 71% and the Y axis was 33%. Based on the overall calculations, it can be concluded that the FLC light tracker has an increase in the speed value of 29% and an increase in the value of accuracy in the accuracy aspect by 35% and the precision aspect by 26% compared to the PID light tracker in previous studies.